(3GdfabGJ GdYGeI,GdGjQGOGJ GdYGeI,GdejRGfjI GdYGeI ddOhdIs - (3eMQRj eMeO(B, (3YHGSs ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2008)
(3eaghe Yde GdeGdjI GdYGeI,GdfabGJ GdYGeI,GdEjQGOGJ GdYGeI,GdejRGfjI GdYGeI ddOhdIs
(3HHdjhZQGajG(B: (3U U(B.385-388s
Keywords: (3GdeGdjI GdYGeIs; (3GdejRGfjIs; (3GdfabGJ GdYGeIs